Pengaruh Dosis Bioaktivator Gliocladium Sp Terhadap Pertumbuhan Benih Kopi Varietas Sigarar Utang Dan Lini S 795 Di Perbenihan - Krisnadi Krisnadi; R. Wahyono Widodo; Agus Surya Mulya (Paspalum: Jurnal Ilmiah Pertanian, 2020)
The important thing in coffee plantation ventures is when preparing coffee seeds such as Sigarar debt and line S 795. Planting Media plays an important role to get good seeds. Bioaktivator Gliocladium sp which is a fungus that can accelerate the process of decomposition of organic matter in nature. The method of research used is experimental design. Research conducted in Plantation PPPPTK Agriculture Cianjur Ministry of Education and Culture. The research draft using a separate tile experiment (Split Plot design) consists of two treatments. The first treatment (main plot) consists of 2 of the Varitas Sigarar debt and line S 795. The second treatment (plot) consists of 5 levels. There are 10 treatment combinations and each of them is 3 repeats so there are 30 units of trial. The number of seeds in research 1500 plants. The free variable i.e. the main tile (v) consists of 2 levels namely V1 = Debt Sigarar Varieties v2 = varieties of line S 795. Child Tile (d) consists of 5 levels ie D0 = 0 gr/kg media cropping (control), D1 = 1 gr/kg of media cropping, D2 = 2 G gr/kg of media planting, D3 = 3 gr/kg of media planting, D4 = 4 gr/kg of planting media. The use of Sigararutang varieties and lines 795 S and the bioactivator dose of Gliocladiun there is no interaction. The results of the self-test varieties all the parameters do not differ real only on the high parameter plant variety line S 795 gives a different plant height than the Sigararutang varieties.  Self-test result dose of bioaktiovator Gliocladium SP dose 4 gr/kg of medium gives high results on all parameters. On the parameters of wet-weights plant dose Bioaktiovator Gliocladium sp not differ in real. Optimum dose of Bioaktiovator Gliocladium sp which produces maximum dry weight respectively on each coffee varieties at a dose of 4 gr/kg of media on the Sigararutang varieties provide a dry weight of 2.42 grams, higher than in line S 795 of 2.24 grams.